Effect of Local Anesthesia with and without the Vasoconstrictor on Blood Glycemic Level in Diabetic Patients Undergoing Tooth Extractions - Sujata Kumari; Chandandeep Singh; Riya Jaitly; Suresh B. Kondaveeti; Mohamed S. M. Morsy; Ahtesham A. Qurishi; Akshaya Ojha (Journal of Pharmacy and Bioallied Sciences)
Background: Vasoconstrictors with local anesthetics provide a bloodless as well as toxicity-free area for effortless extraction tooth. This study was conducted to evaluate the effect of local anesthesia (LA) with adrenaline and without adrenaline on blood glycemic levels in patients undergoing tooth extraction. Material and Method: A total of 120 patients who require multiple extractions consisting of 60 healthy and 60 diabetic patients in need of multiple extractions were selected for this study. Subjects were given plain lignocaine on their 1st visit and tooth extraction was performed. After seven days lignocaine with 1:80,000 adrenaline was administered to the same patient for a similar procedure. Blood glycemic levels were estimated at regular intervals that is before and right away after the administration of LA) 10 and 20 min on both occasions. Results: Comparing the glucose level at 10 min and 20 min showed a statistically significant distinction (P < 0.001) in healthy subjects. Comparing the glucose level at 10 min and 20 min intervals showed highly statistically significant distinction (P < 0.001) in diabetic subjects (P < 0.001). Conclusion: LA with vasoconstrictor leads to an elevation in blood glycemic level in patients with NIDDM.